The changing representation interface: democracy and direct contact with politicians. Issue 1 (2nd January 2016) - Southern, Rosalynd; Purdam, Kingsley
ABSTRACT: The interface between politicians and the electorate is a vital component of the infrastructure of democracy and politicians now have many more tools available to communicate and engage with the electorate. Direct contact between politicians and the electorate is associated with increased levels of civic engagement. In this article, we examine the responsiveness of politicians in the UK by conducting: (i) an innovative test of responses to an undecided voter's email and (ii) follow-up interviews with electoral candidates. We found that a majority of electoral candidates had an identifiable email address and more than half responded to our undecided voter's email. However, there were considerable differences in the content relevance of the responses. There were also very few follow-up emails or further contact from the electoral candidates, suggesting only limited evidence of an integrated communication strategy. Electoral candidates also expressed concerns about communicating in a way that was 'on record'. The findings provide a unique insight into the dynamics of communication between politicians and the electorate and the changing nature of the representation interface. Whilst the Internet has the scope for more personalized and two-way communication and for electors to hold politicians to account, it seems that politicians are more focused on campaign advantage rather than renewing the representation interface.